Green Accounting, Good Corporate Governance dan Nilai Perusahaan: Sustainability Report sebagai Variabel Intervening - Desmiyawati, Desmiyawati; Rofika, Rofika; Humairoh, Fitri; Azlina, Nur; Ramaiyanti, Sinta (Akuntansi & Ekonomika, 2025)
This study aims to test the effect of green accounting and good corporate governance on company value mediated by sustainability reports. The method used in this research is a quantitative methods with secondary data. The population in this study were companies listed on the IDX Energy Sector totaling 81 companies. The sample determination used the purposive sampling method, resulting in 43 company samples determined with a total of 3 years of observation so that the total data was 129. The testing method used was PLS analysis. The results of the study showed that green accounting and good corporate governance (GCG) had a significant effect on company value and sustainability reports in energy sector companies. GCG showed a significant effect on company value and sustainability reports. However, sustainability reports do not mediate the effect of green accounting and GCG on company value.